Pengaruh Sertifikasi Halal dan Religusitas terhadap Niat Beli dengan Mediasi Kepercayaan pada Produk Kosmetik Halal - Dwi Anggita, Ajeng; Astuti, Budi (Universitas Hamzanwadi, 2024)
Indonesia, with a large Muslim population, means that halal cosmetic products are increasingly developing. However, generation Z, which is a significant market segment, tends to be less enthusiastic about exploring further information about the halalness of a product. The aim of the research is to determine the intention to purchase halal cosmetic products among generation Z Muslims. The total sample was 146 respondents, obtained through the accidental sampling method. Based on primary data, obtained through a Likert scale questionnaire with Partial Least Square (PLS), the results were obtained: halal certification has a positive and significant effect on trust, trust does not have a positive and significant effect on the intention to purchase halal cosmetic products, trust does not mediate the effect of halal certification on intention to buy halal cosmetic products, halal certification does not have a positive and significant effect on intention to buy halal cosmetic products, intention to buy has a positive and significant effect on consumer buying behavior, religiosity has a positive and significant effect on intention to buy halal cosmetic products. With these results, halal product marketers can use them in developing policies and marketing strategies